The Higgs boson couplings: past, present, and future. The relationships between Higgs boson and other known particles as measured by current and future experiments - Ortona, Giacomo (Frontiers in Physics, 2023)
The discovery of the Higgs boson, a fundamental particle of the Standard Model, at the Large Hadron Collider (LHC) in 2012, marked a monumental milestone in the field of particle physics. Since then, extensive research has been conducted to understand the properties and interactions of the Higgs boson, particularly its couplings with other known particles. This article provides a review of the past, present, and future measurements of the Higgs boson couplings, with a focus on the most recent experimental developments. It discusses the experimental techniques and methods used to study the Higgs boson couplings, including the production and decay channels employed in various experiments. The article highlights the important relationships between the Higgs boson and other known particles, including the gauge bosons (W and Z bosons), quarks, and leptons and the Higgs boson itself, through its self-interaction. After discussing the channels used by ATLAS and CMS collaborations to measure the Higgs boson coupling to the other standard model particles, the article will present an overview of the latest results obtained at the LHC, commenting on how various measurements have evolved over time along with a better comprehension of the detectors and ever more refined analysis techniques. Future collider developments and expectation for the measurement of the Higgs boson couplings and double-Higgs boson production with increased precision and accuracy will be discussed along with the main challenges faced by future experiments.